Association of DSM-IV posttraumatic stress disorder with traumatic experience type and history in the World Health Organization World Mental Health surveys - Liu, H. (2017)
Importance: Previous research has documented significant variation in the prevalence of posttraumatic stress disorder (PTSD) depending on the type of traumatic experience (TE) and history of TE exposure, but the relatively small sample sizes in these studies resulted in a number of unresolved basic questions. Objective: To examine disaggregated associations of type of TE history with PTSD in a large cross-national community epidemiologic data set. Design, setting, and participants: TheWorld Health OrganizationWorld Mental Health surveys assessed 29 TE types (lifetime exposure, age at first exposure) with DSM-IV PTSD that was associated with 1 randomly selected TE exposure (the random TE) for each respondent. Surveys were administered in 20 countries (n = 34 676 respondents) from 2001 to 2012. Data were analyzed from October 1, 2015, to September 1, 2016. Main outcomes and measures: Prevalence of PTSD assessed with the Composite International Diagnostic Interview. Results: Among the 34 676 respondents (55.4%[SE, 0.6%] men and 44.6%[SE, 0.6%] women; mean [SE] age, 43.7 [0.2] years), lifetime TE exposure was reported by a weighted 70.3%of respondents (mean [SE] number of exposures, 4.5 [0.04] among respondents with any TE). Weighted (by TE frequency) prevalence of PTSD associated with random TEs was 4.0%. Odds ratios (ORs) of PTSD were elevated for TEs involving sexual violence (2.7; 95%CI, 2.0-3.8) and witnessing atrocities (4.2; 95%CI, 1.0-17.8). Prior exposure to some, but not all, same-type TEs was associated with increased vulnerability (eg, physical assault; OR, 3.2; 95%CI, 1.3-7.9) or resilience (eg, participation in sectarian violence; OR, 0.3; 95%CI, 0.1-0.9) to PTSD after the random TE. The finding of earlier studies that more general history of TE exposure was associated with increased vulnerability to PTSD across the full range of random TE types was replicated, but this generalized vulnerability was limited to prior TEs involving violence, including participation in organized violence (OR, 1.3; 95%CI, 1.0-1.6), experience of physical violence (OR, 1.4; 95%CI, 1.2-1.7), rape (OR, 2.5; 95%CI, 1.7-3.8), and other sexual assault (OR, 1.6; 95%CI, 1.1-2.3). Conclusion and relevance: The World Mental Health survey findings advance understanding of the extent to which PTSD risk varies with the type of TE and history of TE exposure. Previous findings about the elevated PTSD risk associated with TEs involving assaultive violence was refined by showing agreement only for repeated occurrences. Some types of prior TE exposures are associated with increased resilience rather than increased vulnerability, connecting the literature on TE history with the literature on resilience after adversity. These results are valuable in providing an empirical rationale for more focused investigations of these specifications in future studies. © 2017 American Medical Association.